The Limitations of Symptom-based Heart Failure Management - Lampros Papadimitriou; Charles K Moore; Javed Butler; Robert C Long (Cardiac Failure Review)
Heart failure (HF) has emerged as a global epidemic and it affects about 6 million adults in the US. HF medical treatment, as recommended in guidelines, significantly improves survival and quality of life; however, the mortality burden of HF remains high. For decades, treatment has been guided, mainly by symptoms, leading to undertreatment in a range of settings. Current evidence emphasises the unfavourable outcomes of HF even in early stages or in patients who achieve reverse remodeling and remission or recovery under optimised treatment. This should stimulate efforts towards a more objective, rigorous management, covering the entire spectrum of mild, moderate and severe HF.